2017
DOI: 10.5551/jat.38216
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lomitapide in Japanese Patients with Homozygous Familial Hypercholesterolemia

Abstract: Aim: There is an unmet need in Japan for more optimal lipid-lowering therapy (LLT) for patients with homozygous familial hypercholesterolemia (HoFH) who respond inadequately to available drug therapies and/or apheresis, to achieve goals of low-density lipoprotein cholesterol (LDL-C) reduction by 50% or to < 100 mg/dL.Methods: In this study, Japanese patients with HoFH on stable LLT and diet were treated with lomitapide, initiated at 5 mg/day and escalated to maximum tolerated dose (up to 60 mg/day) over 14 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 27 publications
0
48
0
Order By: Relevance
“…A retrospective study found that the administration of statin and other drugs was effective in reducing mortality rates in HoFH 883 ) . It has been reported that MTP inhibitors, which were developed for HoFH patients, lowered LDL-C by approximately 50% 693 , 884 ) . However, as the frequencies of the adverse events of fatty liver and diarrhea are high, it is essential to control the fat and alcohol intake strictly.…”
Section: Familial Hypercholesterolemiamentioning
confidence: 99%
“…A retrospective study found that the administration of statin and other drugs was effective in reducing mortality rates in HoFH 883 ) . It has been reported that MTP inhibitors, which were developed for HoFH patients, lowered LDL-C by approximately 50% 693 , 884 ) . However, as the frequencies of the adverse events of fatty liver and diarrhea are high, it is essential to control the fat and alcohol intake strictly.…”
Section: Familial Hypercholesterolemiamentioning
confidence: 99%
“…The microsomal triglyceride transfer protein inhibitor, lomitapide, is an orally administered agent and the mechanism underlying its LDL-C lowering effect is independent of LDL receptor activation. However, abdominal pain, diarrhea, liver dysfunction and fatty liver have been reported as adverse effects of this drug and although it has been already approved for use in adult patients with HoFH in Japan, it is not approved for childhood HoFH at present 40 , 41 ) .…”
Section: Treatment Of Pediatric Fhmentioning
confidence: 99%
“…When ineffective, useless continuation of PCSK9 inhibitors is not advisable, and genetic testing should be considered for the possibility of FH homozygote 5 ) . If the diagnosis is FH homozygote, consider treatment not dependent on LDL receptor function such as MTP inhibitors 6 ) (after obtaining authorization for treatment of designated intractable disease) and LDL apheresis.…”
Section: Future Issuesmentioning
confidence: 99%